Critical limits of soil physical attributes for corn and black oat in a Xanthic Hapludox - Eloi Bareta Junior; Aline Marques Genú; Leandro Rampim; Renan Caldas Umburanas; Cristiano Andre Pott (Revista Ciência Agronômica, 2021)
ABSTRACT Soil compaction can decrease potential crop yield and is frequently found in no-till cultivation systems, but there is little information on the critical limits of soil physical properties in these conditions, especially in subtropical soils. The objectives of this study were to evaluate the influence of tractor traffic on soil physical properties and identifies critical limits of soil bulk density, soil compaction degree, macro, and microporosity on crop yield of corn and black oat assessed in situ in a Xanthic Hapludox in Southern Brazil. Tractor machine traffic (0, 2, 5 and 20 passes) was established in no-till soil to create different soil compaction levels. Undisturbed soil samples were collected at depths of 0.00-0.05, 0.07-0.12 and 0.17-0.22 m just after tractor traffic in two moments: before corn cultivation, and then before black oat cultivation. Under the conditions of this experiment, the 10% higher yields of corn and black oats were obtained with macroporosity above 0.10 m3 m-3 and 0.13 m3 m-3, respectively. Similarly, the soil compactness degrees of 90% and 86% were considered critical for the corn and black oat, respectively. In addition, soil compaction by machine traffic reduced maize yield up to 33% and black oat biomass yield up to 44%. Our results demonstrate that growers should be aware of the consequences of machine traffic on soil properties, as it can severely compromise crop yields, especially of corn and black oats cultivated in very clayey soil like the one evaluated in this study.